2004
DOI: 10.1038/sj.npp.1300500
|View full text |Cite
|
Sign up to set email alerts
|

Nonstereotyped Responding in Positive Schizotypy after a Single Dose of Levodopa

Abstract: Stereotyped behavior and left-sided orientation biases, associated with the dopamine (DA) system, were observed in populations of the schizophrenia spectrum disorders. We investigated whether heightened DA concentrations influence both side biases and stereotyped responding in a visuo-motor computer task, in which 90, 180, and 2701 rotated objects had to be brought into a target position. To account for the role of the schizophrenia spectrum, task performance was also analyzed as a function of healthy particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 78 publications
1
15
1
Order By: Relevance
“…The lower sensitivity in the levodopa than placebo group was dependent on participantsʼ paranormal belief. Links between the emergence of paranormal belief and the DA system have been suggested (Brugger & Graves, 1997a) and tested (Mohr et al, 2004;Kumari et al, 1999). Here, contrary to our expectation, a reduced sensitivity in the levodopa as compared to the placebo group was only evident in the skeptics.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The lower sensitivity in the levodopa than placebo group was dependent on participantsʼ paranormal belief. Links between the emergence of paranormal belief and the DA system have been suggested (Brugger & Graves, 1997a) and tested (Mohr et al, 2004;Kumari et al, 1999). Here, contrary to our expectation, a reduced sensitivity in the levodopa as compared to the placebo group was only evident in the skeptics.…”
Section: Discussioncontrasting
confidence: 94%
“…Immediately after behavioral testing, a second sample was drawn. Blood plasma was separated by centrifugation, and the samples were immediately frozen at −80°C for later high-pressure liquid chromatography for electrochemical detection (see Mohr, Landis, Sandor, Fathi, & Brugger, 2004 for further details). No levodopa was detected in the placebo group.…”
Section: L-dopa Blood Serum Concentrations and Efficacy Of Double Blimentioning
confidence: 99%
“…Indeed, behavioural evidence suggests that schizotypy (and schizotypal personality disorder) is associated with aberrant dopamine function (e.g. Mohr et al, 2004;McClure et al, 2010). Mohr et al (2004) demonstrated that levodopa (a dopamine agonist) improved visuo-motor performance exclusively in participants with high 'positive' schizotypy (i.e.…”
Section: Estradiol Might Influence Memory Via Dopaminergic Actionsmentioning
confidence: 99%
“…Mohr et al, 2004;McClure et al, 2010). Mohr et al (2004) demonstrated that levodopa (a dopamine agonist) improved visuo-motor performance exclusively in participants with high 'positive' schizotypy (i.e. magical ideation); low schizotypy participants showed a slight performance deterioration with levodopa.…”
Section: Estradiol Might Influence Memory Via Dopaminergic Actionsmentioning
confidence: 99%
See 1 more Smart Citation